Asymmetric dominance and asymmetric mate choice oppose premating isolation after allopatric divergence - Sefc, Kristina M (Ecol Evol, 2015)
Assortative mating promotes reproductive isolation and allows allopatric speciation processes to continue in secondary contact. As mating patterns are determined by mate preferences and intrasexual competition, we investigated male–male competition and behavioral isolation in simulated secondary contact among allopatric populations. Three allopatric color morphs of the cichlid fish Tropheus were tested against each other. Dyadic male–male contests revealed dominance of red males over bluish and yellow-blotch males. Reproductive isolation in the presence of male–male competition was assessed from genetic parentage in experimental ponds and was highly asymmetric among pairs of color morphs. Red females mated only with red males, whereas the other females performed variable degrees of heteromorphic mating. Discrepancies between mating patterns in ponds and female preferences in a competition-free, two-way choice paradigm suggested that the dominance of red males interfered with positive assortative mating of females of the subordinate morphs and provoked asymmetric hybridization. Between the nonred morphs, a significant excess of negative assortative mating by yellow-blotch females with bluish males did not coincide with asymmetric dominance among males. Hence, both negative assortative mating preferences and interference of male–male competition with positive assortative preferences forestall premating isolation, the latter especially in environments unsupportive of competition-driven spatial segregation.